The Risk Factors That Affecting Carpal Tunnel Syndrome (CTS) - Agusni Karma; Tri Riana Lestari; Ujang Abdul Muis; Rizki Rohimah (Journal of Global Pharma Technology, 2020)
Introduction: Nowadays, interaction between human and mechine is often happened, it can be with computer or laptop, using computer/laptop with mouse in long period without resting the wrist will lead to symptom of Carpal Tunnel Syndrome (CTS). CTS have a significant correlation with improper posture of the hand and the age. This research is to know the relation between age, improper hand position, and work period towards risk of CTS on staffs who work in front of computer/laptop >4 hours a day. Methods: For the method was give some questionnaires, direct observation and Phallen test to each respondent. Results: From 33 of respondents was found 26 staffs who had risk of CTS. In improper hand position and work period factor was found the p-value of 0.000. But in the age factor was found p-value of 0.277. Analysis: In improper hand position and work period factor it caused by wrong position of the hand and pressure median nerve. In the age factor it caused due to staffs often did wrist gymnastic on work hours which is one of the exercises that preventing CTS. Conclusion: There is correlation between improper hand position and work period with risk of CTS. Keywords: Carpal Tunnel Syndrome, Improper Hand Position, Work Period